THE FUTURE OF INTERRELIGIOUS DIALOGUE: THREATS AND PROMISES - Alphonsus Mathias (Journal of Dharma, 1994)
The main threats to interreligious dialogue. if I put into one sentence. are rampant communilisam. religious fundamentalism. culture of hatred and culture of violence. Under these four heads. I can gather all the clouds that are roaming large in the field of interreligious dialogue in this country. And my assertion and affirmation. is that religion is the greatest force that can bind people; it is the greatest force that can touch the minds and hearts; it is the greatest force that can bring in a total change in the whole scenario of our country. And if you say that it is an over statement.